The added value of internal auditing in reducing creative accounting practices - Taha, Mozamil Awad (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to demonstrate the role of internal auditing in reducing creative accounting practices, which is considered one of the most important causes of financial collapse. To achieve the objective of the study, a questionnaire was used and applied to the study sample in order to study the independent variable, the added value of internal auditing. The modified Jones model 1995 was also applied to the financial statements for a period of five years. Years (2017-2021) for a number of five Sudanese banks listed on the Khartoum Stock Exchange to determine whether there are creative accounting practices, Logistic regression analysis was also applied to find out the impact of the independent variable on the dependent variable. The researcher used the quantitative and deductive method in the study. The study concluded a number of results, the most important of which is that the internal audit through its activities plays a major role in reducing creative accounting practices. The study concluded with a number of recommendations, the most important of which are: The need for internal auditors to continuously develop their knowledge and professional capabilities to keep abreast of all new requirements, standards and rules governing their professional behavior and enabling them to perform their tasks with the required quality. Banks are also committed to disclosure requirements and providing all accounting information as the reasons for change in the accounting methods used to reveal creative accounting practices.